TRAINING METHODOLOGY FOR BEGINNER BASKETBALL PLAYERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The development of beginner basketball players requires a structured and scientifically grounded training methodology. This study examines key principles, techniques, and pedagogical approaches used in training novice players. Emphasis is placed on skill acquisition, physical conditioning, and psychological development. The findings suggest that a progressive, age-appropriate, and integrated training system significantly enhances player performance and long-term development.